2009
DOI: 10.1039/b916558d
|View full text |Cite
|
Sign up to set email alerts
|

A rearrangement of 1,1-linked four-membered rings to bicyclic bridgehead five-membered rings: A phosphorus turn

Abstract: Novel rearrangements of 2,3,2',3'-tetra-tert-butyl-4,4'-bis-trimethylsilanyloxy-1,2,1',2'-tetrahydro-[1,1']biphosphetyl (7) to 1,2,5,6-tetra-tert-butyl-3,7-bis-trimethylsilanyloxy-1H,5H-[1,2]diphospholo-[1,2-a][1,2]diphosphole (9) and of 3,4,3,4-tetra-tert-butyl-[1,1']biphosphetanyl-2,2'-dione (10) to 2,3,6,7-tetra-tert-butyl-tetrahydro-[1,2]diphospholo[1,2-a][1,2]diphosphole-1,5-dione (12) were observed during sublimation at 150 degrees C in 0.1 mm vacuum. The C-P-C internal angles of the four-membered rings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Formally, compound 10 can be considered as a dimerization product of intermediate phosphalkyne sulfide 9 with two additional hydrogen abstractions probably from the solvent. The similar rearrangements and plausible mechanisms have been reported by us for analogous tervalent phosphorus systems, which have a tendency to form stable five‐membered bridgehead bicyclic rings, e.g., compound 11 9.…”
Section: Resultssupporting
confidence: 83%
“…Formally, compound 10 can be considered as a dimerization product of intermediate phosphalkyne sulfide 9 with two additional hydrogen abstractions probably from the solvent. The similar rearrangements and plausible mechanisms have been reported by us for analogous tervalent phosphorus systems, which have a tendency to form stable five‐membered bridgehead bicyclic rings, e.g., compound 11 9.…”
Section: Resultssupporting
confidence: 83%
“…[7] For diphosphapentalene derivatives that possesst wo phosphorus(III) atoms at the bridgehead, [8] four major ring systems III-VI have been structurally characterized ( Figure 1b). [9][10][11][12] However,s tudies on their reactivities have been limited to the coordinationn atures towards transition metals, [8b, 11g, 12] their oxidation, [8a, 11 f, 12] and reaction with Grignardr eagents, [10a-c] and thus still remainu nexplored. Considering the importance of phosphorus heterocycles, both the development of unique molecular frameworks and ad eep comprehension of their reactivities are essential to broadening their diversity from afundamental point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The doublet for the phosphaalkene carbon atom in the four‐membered ring appears at δ =244.6 ppm ( 1 J (P,C)=75.7 Hz) in the 13 C{ 1 H} NMR spectrum. This is downfield shifted of the respective signals in five‐membered heterocycles with a phosphoruscarbon double bond ( δ =211–213 ppm)20 and still downfield shifted from a four‐membered heterocycle with a phosphoruscarbon double bond ( δ =234.9 ppm, 1 J (P,C)=41.2 Hz) 21. These analyses clearly showed that a [2+2] cycloaddition and concomitant TMSCl elimination occurred.…”
Section: Resultsmentioning
confidence: 80%
“…The significantly smaller O1‐Si1‐P1 angle in compound 5 compared with compound 6 (77.60(7) and 77.60(6)° vs. 112.2(2)°, respectively) is likely due to the different coordination number of the silicon atom (five in compound 5 and four in compound 6 ). The angle on the phosphorus atom is comparable to another four‐membered ring with a CP bond (C‐P‐C 76.9(1)°) 21. The t Bu group on the carbon atom is bent toward the oxygen atom and thus away from the phosphorus atom (C17‐C16‐P1: 130.5(2) and 131.1(2)° vs. C17‐C16‐O1: 115.6(2) and 115.2(2)°), which was previously observed for another PCO heterocycle (C‐C‐P: 131.75(14)° vs. C‐C‐O: 113.4(2)°) 20a…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation